Designing FRBR-based information visualization for library resources - Ahmad Nawawi, Nur Syahirah; Sarif Abdullah, Sharifah Nur Amirah (myHCI-UX, 2023)
The Functional Requirements for Bibliographic Records (FRBR) model has emerged as a significant framework for bibliographic control, offering a conceptual structure to organize and retrieve bibliographic information effectively. This study explores the potential of FRBR as a tool for information visualization in the domain of bibliographic control. Although bibliographic information systems are important for finding and exploring library resources, some of the fundamental functionality that should be provided to aid users in their information seeking process is still absent. The objectives of this research are to investigate how FRBR can be employed to enhance the visualization of bibliographic data, examine the impact of FRBR on information organization and retrieval along with identify and analyze the challenges associated with FRBR implementation. The analysis of the study is gained through reviewing of existing literature; thus, three main aspects have been presented within the study which are FRBR interface, the impact of FRBR and the challenges of FRBR.